Effect of Aerobic Fermentation on Total Phenolic, Flavonoid, and Antioxidant Activity of Leucaena leucocephala (Lam.) de Wit - Dewantara, Jeisen Pajar; Marpaung, Mauritz Pandapotan; Khairunnisa; Hidayati, Nurul; Setiawansyah, Arif (Universitas Islam Negeri Alauddin Makassar, 2025)
Introduction: Leucaena leucocephala (Lam.) de Wit., commonly known as the petai cina plant, contains significant concentrations of bioactive compounds, particularly flavonoids and phenolic compounds, and demonstrates substantial antioxidant properties. These beneficial compounds, however, can be significantly influenced by various processing methods, with fermentation during simplicia preparation being a notable factor. Aims: This research investigated the impact of fermentation on three key characteristics of petai cina leaf extract: total flavonoid content, total phenolic content, and antioxidant activity. Methods: The study utilized experimental methodology, incorporating both qualitative and quantitative analyses to evaluate these properties. The results revealed that five days fermentation demonstrated the highest value of TFC, TPC, and antioxidant activity. Result: The extract yielded a TFC of 279.08 mg QE/g, while TPC measured 282.34 mg GAE/g. The antioxidant activity demonstrated notable potency, with an IC50 and AAI values of 69.66 µg/mL and 0.574. Conclusion: These findings conclusively demonstrate that the fermentation process significantly influences the concentration of flavonoids and phenolic compounds, yet unsignificant impact antioxidant activity in the extract. This enhanced understanding of fermentation's effects on bioactive compounds in L. leucocephala provides valuable insights for optimizing processing methods to maximize the plant's therapeutic potential.